Novel anti-inflammatory activity of epoxyazadiradione against macrophage migration inhibitory factor inhibition of tautomerase and proinflammatory activities of macrophage migration inhibitory factor - Alam, Athar; Haldar, Saikat; Thulasiram, Hirekodathakallu V.; Kumar, Rahul; Goyal, Manish; Iqbal, Mohd Shameel; Pal, Chinmay; Dey, Sumanta; Bindu, Samik; Sarkar, Souvik; Pal, Uttam; Maiti, Nakul C.; et al. (Journal of Biological Chemistry, 2012)
Macrophage migration inhibitory factor (MIF) is responsible for proinflammatory reactions in various infectious and noninfectious diseases. We have investigated the mechanism of anti-inflammatory activity of epoxyazadiradione, a limonoid purified from neem (Azadirachta indica) fruits, against MIF. Epoxyazadiradione inhibited the tautomerase activity of MIF of both human (huMIF) and malaria parasites (Plasmodium falciparum (PfMIF) and Plasmodium yoelii (PyMIF)) non-competitively in a reversible fashion (K-i, 2.11-5.23 mu M). Epoxyazadiradione also significantly inhibited MIF (huMIF, PyMIF, and PfMIF)-mediated proinflammatory activities in RAW 264.7 cells. It prevented MIF-induced macrophage chemotactic migration, NF-kappa B translocation to the nucleus, up-regulation of inducible nitric-oxide synthase, and nitric oxide production in RAW 264.7 cells. Epoxyazadiradione not only exhibited anti-inflammatory activity in vitro but also in vivo. We tested the anti-inflammatory activity of epoxyazadiradione in vivo after co-administering LPS and MIF in mice to mimic the disease state of sepsis or bacterial infection. Epoxyazadiradione prevented the release of proinflammatory cytokines such as IL-1 alpha, IL-1 beta, IL-6, and TNF-alpha when LPS and PyMIF were co-administered to BALB/c mice. The molecular basis of interaction of epoxyazadiradione with MIFs was explored with the help of computational chemistry tools and a biological knowledge base. Docking simulation indicated that the binding was highly specific and allosteric in nature. The well known MIF inhibitor (S, R)-3-(4-hydroxyphenyl)-4,5-dihydro-5-isoxazole acetic acid methyl ester (ISO-1) inhibited huMIF but not MIF of parasitic origin. In contrast, epoxyazadiradione inhibited both huMIF and plasmodial MIF, thus bearing an immense therapeutic potential against proinflammatory reactions induced by MIF of both malaria parasites and human.

Biocatalysis: fungi mediated novel and selective 12 beta- or 17 beta-hydroxylation on the basic limonoid skeleton - Haldar, Saikat; Kolet, Swati P.; Thulasiram, Hirekodathakallu V. (Green Chemistry, 2013)
Basic limonoids carrying a 4,4,8-trimethyl-17-furanylsteroid skeleton are a class of triterpenoids and well-known for their insecticidal as well as a vast array of pharmacological activities. Rare and synthetically challenging 12 beta- and 17 beta-hydroxylation was achieved on the basic limonoid skeleton to produce a novel series of hydroxylated limonoids using fungi-mediated biocatalysis. The fungal system belonging to the genera of Mucor efficiently converted azadiradione, epoxyazadiradione, gedunin and their derivatives into corresponding 12 beta- and/or 17 beta-hydroxy derivatives. The position and stereochemistry of hydroxylation was determined by rigorous spectroscopic and crystallographic studies. This fungi-mediated stereo- and regio-selective hydroxylation process was highly efficient and mild enough to sustain chemically sensitive functional groups around the basic limonoid skeleton. Modifications of specific functional groups and variation in biocatalyst were shown to bring selectivity among 12 beta- or 17 beta-hydroxylation.

Biocatalyst mediated production of 6 beta,11 alpha-dihydroxy derivatives of 4-ene-3-one steroids - Kolet, Swati P.; Niloferjahan, Siddiqui; Haldar, Saikat; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (Steroids, 2013)
Biotransformation of steroids with 4-ene-3-one functionality such as progesterone (I), testosterone (II), 17 alpha-methyltestosterone (III), 4-androstene-3,17-dione (IV) and 19-nortestosterone (V) were studied by using a fungal system belonging to the genera of Mucor (M881). The fungal system efficiently and quantitatively converted these steroids in regio- and stereo-selective manner into corresponding 6 beta,11 alpha-dihydroxy compounds. Time course experiments suggested that the transformation was initiated by hydroxylation at 6 beta- or 11 alpha-(10 beta-hydroxy in case of V) to form monohydroxy derivatives which upon prolonged incubation were converted into corresponding 613,11oc-dihydroxy derivatives. The fermentation studies carried out using 5 L table-top fermentor with substrates (I and II) clearly indicates that 6 beta,11 alpha-dihydroxy derivatives of steroids with 4-ene-3-one functionality can be produced in large scale by using M881. (C) 2013 Elsevier Ltd.
Keywords: 4-Ene-3-one steroids; Biotransformation; Mucor sp.

Expedient preparative isolation, quantification and characterization of limonoids from neem fruits - Haldar, Saikat; Phapale, Prasad B.; Kolet, Swati P.; Thulasiram, Hirekodathakallu V. (Analytical Methods, 2013)
Major basic limonoids from Neem fruits such as azadirone, epoxyazadiradione and azadiradione were isolated in preparative scale using an automated and rapid medium pressure liquid chromatography (MPLC)-based protocol. They were individually quantified using HPLC. An LC-ESI-MS/MS-based rapid identification technique was developed for the high-throughput screening of these limonoids in phytochemical extracts.

One-pot fluorescent labeling protocol for complex hydroxylated bioactive natural products - Haldar, Saikat; Kumar, Santosh; Kolet, Swati P.; Patil, Harshal S.; Kumar, Dhiraj; Kundu, Gopal C.; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2013)
Tagging of small bioactive molecules with a fluorophore is a highly sensitive method to trace their cellular activities through real-time visual information. Here we disclose a 7-nitrobenzo-2-oxa-1,3-diazole (NBD)-based, high-yielding, one-pot labeling protocol for hydroxylated molecules using Yamaguchi coupling as the key reaction. This methodology was successfully applied on several sensitive and complex hydroxylated bioactive compounds including 7-deacetylazadiradione, simvastatin, camptothecin, andrographolide, cinchonine, beta-dihydroartemisinin, and azadirachtin A. Further, utility of this protocol was illustrated on the cytotoxic activity of azadiradione derivatives against several cancer cell lines through cell imaging of two qualified fluorescent probes.

Biocatalyst mediated functionalization of salannin, an insecticidal limonoid - Haldar, Saikat; Kolet, Swati P.; Dandekar, Devdutta S.; Kale, Balaji S.; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (RSC Advances, 2014)
Transformation of salannin, an insecticidal C-seco limonoid was investigated using a fungal system, Cunninghamella echinulata. Salannin was efficiently converted into two metabolites, where the C-17 furan moiety was transformed into gamma-hydroxybutenolide (salanninolide) and N-(2-hydroxyethyl)-alpha,beta-unsaturated-gamma-lactam (salanninactam) analogues. Present studies have indicated salanninolide to be a metabolite in the C-seco limonoid biosynthetic pathway.

Expedient preparative isolation and tandem mass spectrometric characterization of C-seco triterpenoids from neem oil - Haldar, Saikat; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Dandekar, Devdutta S.; Thulasiram, Hirekodathakallu V. (Journal of Chromatography A, 2014)
C-seco triterpenoids are widely bioactive class of natural products with high structural complexity and diversity. The preparative isolation of these molecules with high purity is greatly desirable, although restricted due to the complexity of natural extracts. In this article we have demonstrated a Medium Pressure Liquid Chromatography (MPLC) based protocol for the isolation of eight major C-seco triterpenoids of salannin skeleton from Neem (Azadirachta indica) oil. Successive application of normal phase pre-packed silica-gel columns for the fractionation followed by reverse phase in automated MPLC system expedited the process and furnished highly pure metabolites. Furthermore, eight isolated triterpenoids along with five semi-synthesized derivatives were characterized using ultra performance liquid chromatography-electrospray ionization-quadrupole/orbitrap-MS/MS spectrometry as a rapid and sensitive identification technique. The structure-fragment relationships were established on the basis of plausible mechanistic pathway for the generation of daughter ions. The MS/MS spectral information of the triterpenoids was further utilized for the identification of studied molecules in the complex extract of stem and bark tissues from Neem. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ESI(+)-quadrupole/orbitrap-MS/MS; MPLC; Neem oil; Preparative isolation; Salannin; Triterpenoids

Lipase mediated separation of triterpene structural isomers, alpha- and beta-amyrin - Haldar, Saikat; Kale, Balaji S.; Jadhav, Dipesh D.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2014)
Pentacyclic triterpenoids alpha- and beta-amyrin possess a wide range of biological and pharmacological activities. High structural similarity between these two structural isomers makes their chromatographic separation an ineffective and tedious choice. In this study, Candida rugosa lipase catalyzed separation protocol for the isolation of individual isomers has been developed. In the presence of vinyl acetate as the acyl donor, Candida rugosa lipase carried out acetylation of beta-amyrin more efficiently as compared to alpha-amyrin leading to a kinetic separation. The conditions of transesterification reaction were optimized systematically, which was utilized to separate alpha- and beta-amyrin from a mixture obtained from the latex of Plumeria obtusa. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Amyrin; Candida rugosa; Kinetic separation; Lipase; Structural isomer

Mucor hiemalis mediated 14 alpha-hydroxylation on steroids: In vivo and in vitro investigations of 14 alpha-hydroxylase activity - Kolet, Swati P.; Haldar, Saikat; Niloferjahan, Siddiqui; Thulasiram, Hirekodathakallu V. (Steroids, 2014)
Transformation of testosterone and progesterone into synthetically challenging 14 alpha-hydroxy derivatives was achieved by using fungal strain Mucor hiemalis. Prolonged incubation led to the formation of corresponding 6 beta/7 alpha,14 alpha-dihydroxy metabolites. The position and stereochemistry of newly introduced hydroxyl group was determined by detailed spectroscopic analyses. The time course experiment indicated that fungal strain initiated transformation by hydroxylation at 14 alpha-position followed by at 6 beta- or 7 alpha-positions. Studies using cell-free extracts suggest that the 14 alpha-hydroxylase activity is NADPH dependent and belongs to the cytochrome P450 family. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: 14 alpha-Hydroxylase; Biotransformation; Mucor hiemalis; Progesterone; Testosterone

Gedunin and azadiradione: human pancreatic alpha-amylase inhibiting limonoids from neem (azadirachta indica) as anti-diabetic agents - Ponnusamy, Sudha; Haldar, Saikat; Mulani, Fayaj A.; Smita S. Zinjarde; Thulasiram, Hirekodathakallu; RaviKumar, Ameeta (Plos One, 2015)
Human pancreatic alpha-amylase (HPA) inhibitors offer an effective strategy to lower postprandial hyperglycemia via control of starch breakdown. Limonoids from Azadirachta indica known for their therapeutic potential were screened for pancreatic alpha-amylase inhibition, a known anti-diabetic target. Studies were carried out to reveal their mode of action so as to justify their hypoglycemic potential. Of the nine limonoids isolated/semi-synthesized from A. indica and screened for alpha-amylase inhibition, azadiradione and exhibited potential inhibition with an IC50 value of 74.17 and 68.38 mu M, respectively against HPA under in vitro conditions. Further screening on AR42J alpha-amylase secretory cell line for cytotoxicity and bioactivity revealed that azadiradione and gedunin exhibited cytotoxicity with IC50 of 11.1 and 13.4 mu M. Maximal secreted alpha-amylase inhibition of 41.8% and 53.4% was seen at 3.5 and 3.3 mu M, respectively. Michaelis-Menten kinetics suggested a mixed mode of inhibition with maltopentaose (K-i 42.2, 18.6 mu M) and starch (K-i' 75.8, 37.4 mu M) as substrate with a stiochiometry of 1: 1 for both azadiradione and gedunin, respectively. The molecular docking simulation indicated plausible p-alkyl and alkyl-alkyl interactions between the aromatic amino acids and inhibitors. Fluorescence and CD confirmed the involvement of tryptophan and tyrosine in ligand binding to HPA. Thermodynamic parameters suggested that binding is enthalpically and entropically driven with Delta G degrees of -21.25 kJ mol(-1) and -21.16 kJ mol(-1) for azadiradione and gedunin, respectively. Thus, the limonoids azadiradione and gedunin could bind and inactivate HPA (anti-diabetic target) and may prove to be lead drug candidates to reduce/control post-prandial hyperglycemia.

Triterpenoid profiling and functional characterization of the initial genes involved in isoprenoid biosynthesis in neem (Azadirachta indica) - Pandreka, Avinash; Dandekar, Devdutta S.; Haldar, Saikat; Uttara, Vairagkar; Vijayshree, Shinde G.; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Thulasiram, Hirekodathakallu V. (BMC Plant Biology, 2015)
Background: Neem tree (Azadirachta indica) is one of the richest sources of skeletally diverse triterpenoids and they are well-known for their broad-spectrum pharmacological and insecticidal properties. However, the abundance of Neem triterpenoids varies among the tissues. Here, we delineate quantitative profiling of fifteen major triterpenoids across various tissues including developmental stages of kernel and pericarp, flower, leaf, stem and bark using UPLC-ESI (+)-HRMS based profiling. Transcriptome analysis was used to identify the initial genes involved in isoprenoid biosynthesis. Based on transcriptome analysis, two short-chain prenyltransferases and squalene synthase (AiSQS) were cloned and functionally characterized. Results: Quantitative profiling revealed differential abundance of both total and individual triterpenoid content across various tissues. RNA from tissues with high triterpenoid content (fruit, flower and leaf) were pooled to generate 79.08 million paired-end reads using Illumina GA.. platform. 41,140 transcripts were generated by d e novo assembly. Transcriptome annotation led to the identification of the putative genes involved in isoprenoid biosynthesis. Two short-chain prenyltransferases, geranyl diphosphate synthase (AiGDS) and farnesyl diphosphate synthase (AiFDS) and squalene synthase (AiSQS) were cloned and functionally characterized using transcriptome data. RT-PCR studies indicated five-fold and ten-fold higher relative expression level of AiSQS in fruits as compared to leaves and flowers, respectively. Conclusions: Triterpenoid profiling indicated that there is tissue specific variation in their abundance. The mature seed kernel and initial stages of pericarp were found to contain the highest amount of limonoids. Furthermore, a wide diversity of triterpenoids, especially C-seco triterpenoids were observed in kernel as compared to the other tissues. Pericarp, flower and leaf contained mainly ring-intact triterpenoids. The initial genes such as AiGDS, AiFDS and AiSQS involved in the isoprenoids biosynthesis have been functionally characterized. The expression levels of AiFDS and AiSQS were found to be in correlation with the total triterpenoid content in individual tissues.
Keywords: Azadirachta indica; Quantitative profiling; Transcriptome; Triterpenoids

Whole-cell mediated 11 beta-hydroxylation on the basic limonoid skeleton by cunninghamella echinulata - Haldar, Saikat; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2015)
Regio- and stereoselective 11 beta-hydroxylation was achieved on the basic limonoid skeleton through microbial transformation. Whole cells of Cunninghamella echinulata efficiently converted basic limonoids such as epoxyazadiradione, azadiradione, and gedunin to their 11 beta-hydroxy analogues as the sole metabolite. Fermentation conditions affecting the efficiency (96%) of biotransformation including substrate concentration, incubation period, pH, and temperature were optimized. The position and stereochemistry of hydroxyl functionality on the isolated metabolites were established through extensive spectroscopic and spectrometric studies (1D, 2D NMR, ESI-MS, and MS/MS).

Azadirachta indica triterpenoids promote osteoblast differentiation and mineralization in vitro and in vivo - Kushwaha, Priyanka; Khedgikar, Vikram; Haldar, Saikat; Gautam, Jyoti; Mulani, Fayaj A.; Thulasiram, Hirekodathakallu V.; Trivedi, Ritu (Bioorganic & Medicinal Chemistry Letters, 2016)
Terpenoids were isolated using chromatographic purification through solvent purification technique and identified as Azadirone (1), Epoxyazadiradione (2) Azadiradione (3) Gedunin (4) Nimbin (5) Salannin (6) Azadirachtin A (7) and Azadirachtin B (8) from Azadirachta indica. Out of eight compounds, only three compounds had osteogenic activity and enhanced osteoblast proliferation, differentiation and mineralization in osteoblast cells. Active compounds stimulated osteogenic genes ALP, RunX-2 and OCN expressions in vitro, but Azadirachtin A had a maximum ability to stimulate osteoblast differentiation and mineralization compared to other two active compounds. For in vivo study, Azadirachtin A injected subcutaneously in pups, which enhanced osteogenic gene expressions and promoted bone formation rate significantly. Here, we conclude that active compounds of Azadirachta indica have osteogenic activity and Azadirachtin A has a beneficial effects on bone. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: ALP and mineralization assay; Balb/c mice pups; Calvarial osteoblast cells; Gene expressions

Epoxyazadiradione suppresses breast tumor growth through mitochondrial depolarization and caspase-dependent apoptosis by targeting PI3K/Akt pathway - Kumar, Dhiraj; Haldar, Saikat; Gorain, Mahadeo; Kumar, Santosh; Mulani, Fayaj A.; Yadav, Amit S.; Miele, Lucio; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (BMC Cancer, 2018)
Background: Breast cancer is one of the most commonly diagnosed invasive cancers among women around the world. Among several subtypes, triple negative breast cancer (TNBC) is highly aggressive and chemoresistant. Treatment of TNBC patients has been challenging due to heterogeneity and devoid of well-defined molecular targets. Thus, identification of novel effective and selective agents against TNBC is essential. Methods: We used epoxyazadiradione to assess the cell viability, mitochondrial potential, ROS level, cell migration, apoptosis and protein expression in cell culture models of TNBC MDA-MB-231 and ER+MCF-7 breast cancer cells. The molecular mechanism was examined in two different type of breast cancer cells in response to epoxyazadiradione. We have also analyzed the effect of epoxyazadiradione on breast tumor growth using in vivo mice model. Results: In this study, we for the first time investigated that out of 10 major limonoids isolated from Azadirachta indica, epoxyazadiradione exhibits most potent anti-cancer activity in both TNBC and ER+breast cancer cells. Epoxyazadiradione induces apoptosis and inhibits PI3K/Akt-mediated mitochondrial potential, cell viability, migration and angiogenesis. It also inhibits the expression of pro-angiogenic and pro-metastatic genes such as Cox2, OPN, VEGF and MMP-9 in these cells. Furthermore, epoxyazadiradione attenuates PI3K/Akt- mediated AP-1 activation. Our in vivo data revealed that epoxyazadiradione suppresses breast tumor growth and angiogenesis in orthotopic NOD/SCID mice model. Conclusion: Our findings demonstrate that epoxyazadiradione inhibits PI3K/Akt-dependent mitochondrial depolarisation, induces apoptosis and attenuates cell migration, angiogenesis and breast tumor growth suggesting that this compound may act as a potent therapeutic agent for the management of breast cancer.
Keywords: Angiogenesis; Apoptosis; Breast cancer; Limonoids; Metastasis; PI3K

Tracing the biosynthetic origin of limonoids and their functional groups through stable isotope labeling and inhibition in neem tree (Azadirachta indica) cell suspension - Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Pandreka, Avinash; Kumar, Ashish; Nandikol, Sharvani S.; Haldar, Saikat; Thulasiram, Hirekodathakallu V. (BMC Plant Biology, 2018)
Background Neem tree serves as a cornucopia for triterpenoids called limonoids that are of profound interest to humans due to their diverse biological activities. However, the biosynthetic pathway that plant employs for the production of limonoids remains unexplored for this wonder tree. Results Herein, we report the tracing of limonoid biosynthetic pathway through feeding experiments using C-13 isotopologues of glucose in neem cell suspension. Growth and development specific limonoid spectrum of neem seedling and time dependent limonoid biosynthetic characteristics of cell lines were established. Further to understand the role of mevalonic acid (MVA) and methylerythritol phosphate (MEP) pathways in limonoid biosynthesis, Ultra Performance Liquid Chromatography (UPLC)- tandem mass spectrometry based structure-fragment relationship developed for limonoids and their isotopologues have been utilized. Analyses of labeled limonoid extract lead to the identification of signature isoprenoid units involved in azadirachtin and other limonoid biosynthesis, which are found to be formed through mevalonate pathway. This was further confirmed by treatment of cell suspension with mevinolin, a specific inhibitor for MVA pathway, which resulted in drastic decrease in limonoid levels whereas their biosynthesis was unaffected with fosmidomycin mediated plastidial methylerythritol 4-phosphate (MEP) pathway inhibition. This was also conspicuous, as the expression level of genes encoding for the rate-limiting enzyme of MVA pathway, 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGR) was comparatively higher to that of deoxyxylulose-phosphate synthase (DXS) of MEP pathway in different tissues and also in the in vitro grown cells. Thus, this study will give a comprehensive understanding of limonoid biosynthetic pathway with differential contribution of MVA and MEP pathways. Conclusions Limonoid biosynthesis of neem tree and cell lines have been unraveled through comparative quantification of limonoids with that of neem tree and through C-13 limonoid isotopologues analysis. The undifferentiated cell lines of neem suspension produced a spectrum of C-seco limonoids, similar to parental tissue, kernel. Azadirachtin, a C-seco limonoid is produced in young tender leaves of plant whereas in the hard mature leaves of tree, ring intact limonoid nimocinol accumulates in high level. Furthermore, mevalonate pathway exclusively contributes for isoprene units of limonoids as evidenced through stable isotope labeling and no complementation of MEP pathway was observed with mevalonate pathway dysfunction, using chemical inhibitors.

Azadirachtin-A from azadirachta indica impacts multiple biological targets in cotton bollworm helicoverpa armigera - Dawkar, Vishal V.; Barage, Sagar H.; Barbole, Ranjit S.; Fatangare, Amol; Grimalt, Susana; Haldar, Saikat; Heckel, David G.; Gupta, Vidya S.; Thulasiram, Hirekodathakallu V.; Svatos, Ales.; Giri, Ashok P. (ACS Omega, 2019)
Azadirachtin-A (AzaA) from the Indian neem tree (Azadirachta indica) has insecticidal properties; however, its molecular mechanism remains elusive. The ``targeted and nontargeted proteomic profiling'', metabolomics, matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) imaging, gene expression, and in silico analysis provided clues about its action on Helicoverpa armigera. Fourth instar H. armigera larvae fed on AzaA-based diet (AzaD) suffered from significant mortality, growth retardation, reduced larval mass, complications in molting, and prolonged development. Furthermore, death of AzaD-fed larvae was observed with various phenotypes like bursting, blackening, and half-molting. Liquid chromatography-mass spectrometry (LC-MS) data showed limited catabolic processing of ingested AzaA and dramatic alternations of primary metabolism in H. armigera. MALDI-TOF imaging indicated the presence of AzaA in midgut of H. armigera. In the gut, out of 79 proteins identified, 34 were upregulated, which were related to digestion, immunity, energy production, and apoptosis mechanism. On the other hand, 45 proteins were downregulated, including those from carbohydrate metabolism, lipid metabolism, and energy transfer. In the hemolymph, 21 upregulated proteins were reported to be involved in immunity, RNA processing, and mRNA-directed protein synthesis, while 7 downregulated proteins were implicated in energy transfer, hydrolysis, lipid metabolism, defense mechanisms, and amino acid storage-related functions. Subsequently, six target proteins were identified using labeled AzaA that interacted with whole insect proteins. In silico analysis suggests that AzaA could be efficiently accommodated in the hydrophobic pocket of juvenile hormone esterase and showed strong interaction with active site residues, indicating plausible targets of AzaA in H. armigera. Quantitative polymerase chain reaction analysis suggested differential gene expression patterns and partly corroborated the proteomic results. Overall, data suggest that AzaA generally targets more than one protein in H. armigera and hence could be a potent biopesticide.

Estrogen receptor activation in response to Azadirachtin A stimulates osteoblast differentiation and bone formation in mice - Kushwaha, Priyanka; Ahmad, Naseer; Dhar, V. Yogeshwar; Verma, Ashwni; Haldar, Saikat; Mulani, Fayaj A.; Trivedi, Prabodh K.; Mishra, Prabhat R.; Thulasiram, V. Hirekodathakallu; Trivedi, Ritu (Journal of Cellular Physiology, 2019)
The positive effectsof the sex hormone in sustaining bone homeostasis areexercised by maintaining the equilibrium betweencell activity and apoptosis. In this regard, the importance of estrogen receptors in maintaining the bone is that it is anattractive drug target,if devoid of known side effects. In this study, we show that a natural pure compound Azadirachtin A (Aza A) isolated from Azadirachta indica binds selectively to a site in the estrogen receptor, identifying itself to bea selective tissue modifier. Using computational and medicinal chemistry, we show that Aza A binds potentially and selectively to estrogen receptor-alpha (ER alpha) as compared with ER beta. This preferential binding of Aza A to ER alpha with good pharmacokinetic distribution in the body forms metabolites, showing that it is well absorbed. In in vivo estrogen deficiency models for osteoporosis, Aza A at a much lower dose enhances new bone formation at both sites of the trabecular and cortical bone with increased bone strength and presentswith no hyperplastic effect in the uterus.
Keywords: ALP; Gene expression; micro-CT; mineralization; osteoblast cells

Accurate identification of bioactive meliaceae limonoids by UHPLC-MS/ms based structure-fragment relationships (SFRs) - Mulani, Fayaj A.; Nandikol, Sharvani S.; Haldar, Saikat; Thulasiram, V, Hirekodathakallu (ACS Omega, 2021)
Y Limonoids are bioactive plant specialized metabolites found in the Meliaceae family. The basic limonoids, i.e., azadiradione, epoxyazadiradione, and gedunin have been exploited for various bioactivities and therefore are the potential drug leads for tomorrow. However, their low abundance, structural similarity, and lack of adequate mass fragmentation data have hampered their accurate identification and quantification from various sources. In the present study, basic limonoids such as azadirone, azadiradione, epoxyazadiradione, and gedunin isolated from Neem were utilized for the synthesis of their derivatives and isotopologs. A total of 30 one compounds were used in this study among which five were isolated, two were biotransformed, and 24 were synthesized. Among the synthesized compounds nine are novel compounds including six deuterated analogs/isotopologs which are (1,3-H-2)-1,2dihydro-3 beta-hydroxyazadiradione (9), (1,3,16-H-2)-1,2-dihydro-3 beta-16 beta-dihydroxyazadiradione (10), 3 beta-hydroxyazadiradione (11), 3 beta-16 beta-dihydroxyazadiradione (12), (3-H-2)-3 beta-hydroxyazadiradione (13), (3,16-H-2)-3 beta-16 beta-dihydroxyazadiradione (14), (1,3,7-H-2)-1,2-dihydro-3 beta-hydroxy-7-deacetylazadiradione (15), 1,2,20,21,22,23-hexahydroazadiradione (17), and (1,3-H-2)-1,2-dihydro-3 beta-hydroxygedunin (29). These limonoids along with their semisynthesized derivatives were subjected to ultra high performance liquid chromatography mass spectrometry (UHPLC-MS/MS) and the fragmentation pathway was established based on structure-fragment relationships (SFRs), utilizing high resolution MS/MS data. We have developed a most reliable and easily reproducible protocol describing in depth analysis of SFRs based on the structural modifications and synthesis of isotopologs. Also, the MS/MS fragment library of these basic limonoids generated in this study acts as a fingerprint for accurate identification and quantification of limonoids by MS/MS analysis in various plant tissue extracts, phytopharmaceutical formulations and biological samples.